The role of psychological factors in pediatric functional abdominal pain disorders. Issue 6 (6th February 2019) - Newton, Emily; Schosheim, Alex; Patel, Samit; Chitkara, Denesh K.; van Tilburg, Miranda A. L.
Abstract: Background: Pediatric functional abdominal pain disorders (FAPDs) are disorders of brain‐gut dysregulation. Psychological factors are known to be related to etiology, maintenance, and exacerbation of pediatric FAPDs. With the evolving literature in the past two decades, a better understanding has emerged of precisely which psychological factors are associated with childhood FAPDs. Purpose: This narrative literature review summarizes the literature of both child and parent psychological factors in pediatric FAPD. Where anxiety and depression were major targets in the older literature, present‐day focus is increasingly on pain‐specific cognitions and coping strategies including disease threat and catastrophizing. In addition, parental reaction to a child's pain is increasingly recognized as an important moderator of a child's outcomes and has become an area for clinical intervention. Screening for these factors and integrative treatment approaches are recommended in childhood FAPD.